Prebiotics and Probiotics From Food to Health - Franco Robles, Elena (IntechOpen, 2022)
Currently, new health benefits of probiotics have been identified, and new strains with probiotic potential have been discovered and continue to be investigated. Likewise, prebiotics and their interaction with the microbiota have been the focus of research in human and animal health, as well as to counteract zoonotic pathogenic microorganisms. Probiotics and prebiotics can be found in food and are isolated or synthesized to be supplemented as functional ingredients for the benefit of humans or animals. The volume contains thirteen chapters that explain the mechanisms of probiotics, prebiotics, and symbiotics from their interaction with the intestinal microbiota as antimicrobials and immunomodulators and their effect on human and animal health.